Bioethical aspects of therapeutic abortion in girls and adolescents under 15 years of age - ávara Orozco, Luis T (2023)
The objective of this paper is to identify and discuss the scientific and bioethicalarguments that justify therapeutic abortion in girls and adolescents under 15 yearsof age. For this purpose, a non-systematic bibliographic search was made in nationaland foreign sources in the different indexers. It was found that there is sufficientscientific evidence that identifies unintended pregnancy in girls and adolescentsunder 15 years of age as a medical emergency and of high risk due to the differentsevere complications that can occur and bioethical arguments in favor of therapeuticabortion. In conclusion, scientific evidence and bioethical arguments sufficientlysupport therapeutic abortion care for girls and adolescents under 15 years of age.